2016
DOI: 10.1177/1045389x16657426
|View full text |Cite
|
Sign up to set email alerts
|

Deformable force amplification frame promoting piezoelectric stack energy harvesting: Parametric model, experiments and energy analysis

Abstract: This article presents a nonlinear parametric model of force amplification ratio and an electromechanical model to couple the deformable frame with the piezoelectric stack in order to promote high-efficiency energy harvesting from human walking locomotion. Two improved frames (Frames I and II) are developed based on the modeling and simulation results. The experiments verified these modeling and simulation results that improved frames demonstrate a higher amplification ratio (8.4 for Frame II and 8.0 for Frame … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…A piezoelectric stack energy harvester (PSEH) with a mechanical transformer was used to study in this work, which is a good example of strongly coupled PEH. Similar harvesters have been widely studied for low-frequency compressive force energy harvesting [31][32][33][34] due to the high electrical power output, which is a result of the force amplification mechanism and the high electromechanical coupling of piezoelectric stacks used [35].…”
Section: Piezoelectric Stack Energy Harvestermentioning
confidence: 99%
See 3 more Smart Citations
“…A piezoelectric stack energy harvester (PSEH) with a mechanical transformer was used to study in this work, which is a good example of strongly coupled PEH. Similar harvesters have been widely studied for low-frequency compressive force energy harvesting [31][32][33][34] due to the high electrical power output, which is a result of the force amplification mechanism and the high electromechanical coupling of piezoelectric stacks used [35].…”
Section: Piezoelectric Stack Energy Harvestermentioning
confidence: 99%
“…To simplify the analysis, it is assumed that the hinges are free to flexure while the inclined beams do not change its length. In a quasi-static state, the following relationship can be obtained [33,36] 𝐹 𝑧 = 𝐹 𝑥 cot 𝛽 𝐷 𝑥 = 𝐷 𝑧 cot 𝛽 ( 11 ) where 𝐹 𝑥 and 𝐷 𝑥 are the input force and displacement; 𝐹 𝑧 and 𝐷 𝑧 are the force and displacement of the piezoelectric element.…”
Section: Working Mechanismmentioning
confidence: 99%
See 2 more Smart Citations
“…Generally, piezoelectric stack exhibits a higher stiffness and can bear a larger compressive force. Thus, it is expected to produce more power output [14], [15]. Xu et al reported that the energy produced by a piezoelectric stack is proportional to the square of the exerted force [16].…”
Section: Introductionmentioning
confidence: 99%